Wheezing Beyond Bronchial Asthma - Pant, P; Sharma, S; Shrestha, R; Bom, N; Das, S; Yogi, KN (Journal of Institute of Medicine Nepal, 2013)
Churg-Strauss syndrome (CSS) is an eosinophil-associated, small vessel granulomatous vaculitis, characterized by late onset asthma, upper airways disease, eosinophilia, and clinical manifestations of systemic vasculitis. [1,11-13] Diagnosis is mainly clinical with findings of asthma, eosinophilia, rhino sinusitis and signs of vasculitis in major organs. So far to the best of our knowledge reporting of CSS has not been done in Nepal. We here present a case of Churg- Strauss syndrome, a Anti-Neutrophil Cytoplasmic Antibody(ANCA) Associated Vasculities more specifically perinuclear anti-neutrophil cytoplasmic antibodies (p-ANCA) directed against myeloperoxidase (MPO) in a 25years female patient who was initially evaluated for progressive dyspnea, wheeze, cough, joint pain and fever. Regarding the inference drawn from our case report we suggest that patient presenting with the clinical features of asthma needs further evaluation to unmask previously unrecognized underlying Churg-stauss syndrome. DOI: http://dx.doi.org/10.3126/joim.v34i2.9055 Journal of Institute of Medicine August, 2012; 34:2 48-52